Comparison of the effects of diets enriched in lauric, palmitic, or oleic acids on serum lipids and lipoproteins in healthy women and men - Temme, EH; Mensink, RP; Hornstra, G (The American journal of clinical nutrition, 1996)
The degree to which different saturated fatty acids exert their cholesterol-raising effects is still unknown. Therefore, we studied the effect on serum lipids and lipoproteins of diets rich in lauric, palmitic, or oleic acids. Eighteen women and 14 men consumed in random order three experimental diets, each for 6 wk. The diets consisted of solid foods and contained 40% of energy as fat, of which 28% was supplied by the experimental fats. The fat high in lauric acid was a mixture of palm kernel oil (75%) and a high-oleic acid sunflower oil (25%); the fat high in palmitic acid consisted of dairy fat (55%), palmstearin (36%), and sunflower oil (9%); and the fat high in oleic acid consisted of dairy fat (37%) and sunflower oil (63%). The calculated nutrient composition was the same in each diet except for approximately equal to 8.5% of energy, which was provided by lauric, palmitic, or oleic acids. With the lauric acid diet the subjects’ serum total cholesterol concentration increased by 0.22 mmol/L (P = 0.0121; 95% CI: 0.02, 0.41 mmol/L) as compared with the palmitic acid diet and by 0.48 mmol/L (P < 0.0001; 95% CI: 0.29, 0.67 mmol/L) compared with the oleic acid diet. Total cholesterol concentrations with the palmitic acid diet were 0.26 mmol/L (P = 0.0012; 95% CI: 0.07, 0.46 mmol/L) higher than with the oleic acid diet. High-density-lipoprotein (HDL)-cholesterol concentrations increased by 0.12 mmol/L (P = 0.006; 95% CI: 0.04, 0.20 mmol/L) with the lauric acid compared with the palmitic acid diet and by 0.14 mmol/L (P < 0.001; 95% CI: 0.07, 0.22 mmol/L) compared with the oleic acid diet. HDL-cholesterol concentrations with the palmitic acid and the oleic acid diet were the same. No effects were seen in serum triacylglycerol and lipoprotein(a) concentrations. We conclude that both lauric and palmitic acids are hypercholesterolemic compared with oleic acid. Lauric acid raises total cholesterol concentrations more than palmitic acid, which is partly due to a stronger rise in HDL cholesterol.